The frequency of change in five-point scale score with a Bayesian penalised likelihood PET reconstruction algorithm on interim FDG PET-CT and its potential implications for therapy decisions in Hodgkin's lymphoma. Issue 2 (February 2023) - Subesinghe, M.; Ilyas, H.; Dunn, J.T.; Mir, N.; Duran, A.; Mikhaeel, N.G.; Barrington, S.F.
Abstract : Aim: To assess the effect of a Bayesian penalised likelihood (BPL) reconstruction algorithm on the five-point scale (5-PS) score, response categorisation, and potential implications for therapy decisions after interim 2-[ 18 F]-fluoro-2-deoxy-d- glucose (FDG) positron-emission tomography (PET)–computed tomography (CT) (iPET-CT) to guide treatment in classical Hodgkin's lymphoma (HL). Materials and methods: The present study included new patients with HL undergoing iPET-CT from 2014–2019 after two cycles of doxorubicin (Adriamycin), bleomycin, vincristine, and dacarbazine (ABVD). Two reporters categorised response using the 5-PS and measured maximum standardised uptake values (SUVmax ) of the most avid tumour residuum, mediastinal blood pool, and normal liver with ordered subset expected maximisation (OSEM) and BPL reconstructions. Results: Eighty-one iPET-CT examinations were reviewed. Compared with OSEM, BPL increased the 5-PS score by a single score in 18/81 (22.2%) patients. The frequency of potential treatment intensification by changing a score of 3–4 was 13.6% (11/81) and represented 25% (11/44) of patients with a score of 3 on OSEM. All 11 patients remained in remission without a change in therapy (mean 63 months) except one who required second-line treatment for refractory disease. Median SUVmax of tumour residuum was significantly higher with BPL compared with OSEM (2.7 versus 2.4, p<< 0.0001), whilst liver SUVmax was significantly lower for both reporters (up to 6.6%, p< 0.0001). Conclusion: BPL PET reconstruction increased the 5-PS score on iPET-CT in 22% of HL patients and can potentially result in unnecessary treatment escalation in over half of these patients. Highlights: BPL PET reconstruction increases the 5-PS score on iPET-CT in 22% patients with HL. Unnecessary treatment intensification could occur in over half of these patients. BPL increases tumour residuum SUVmax and reduces liver SUVmax . Recommend review of BPL and OSEM reconstructions during iPET-CT interpretation. Recommend use of OSEM reconstruction to clarify discordances in metabolic response.